The position of China in the modern economic space - I. A. Konovalova; M. A. Vorontsova (Вестник Северо-Кавказского федерального университета, 2022)
The current development of the world is conditioned by the processes that take place in developing countries. East Asia today is the central link in the economic growth of the modern world economy. The further development of China is very relevant, since the state is a powerful pole of the world economy, and also claims political leadership. The article considers the current situation of the PRC, studies the results of the development of the country’s leading industries, analyzes the dynamics of real GDP and other macroeconomic indicators for 2016-2021, identifies the problems and advantages of the state, and identifies the reasons for the interaction between Russia and China.